Les femmes et l’impôt sur le revenu - Gauthier, Anne (L'Actualité économique, 1984)
ABSTRACTIn this article, the fiscal system is analyzed critically from the point of view of women as fulltime housewives and mothers. Different personal exemptions and rules of transferability are showned to intensify the economic dependency of housewives and the economic invisibility of their domestic labour. Contrary to accepted opinion, there does not exist any automatic or universal formula for the sharing of income between spouses. In addition, for mothers, in the labour force or not, the costs of providing care for young children in time or money are supported mainly by the women themselves. The author examines different propositions for reform and wishes to restimulate the debate.